EVALUATION OF ANTHELMINTIC ACTIVITY OF MOMORDICA CHARANTIA, CUCURBITA PEPO L., AND SOLANUM TORVUM BASED FORMULATION AND ITS PHYTOCHEMICAL ANALYSIS USING FOURIER TRANSFORM INFRARED - Firdous, Jannathul; V, Bharathi; Muhamad, Noorzaid (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, the phytochemical and anthelmintic effect of a formulation (MCS) prepared from the plants, namely Momordica charantia, Cucurbita pepo L., and Solanum torvum were investigated. Methods: Phytochemical constituents were analyzed using Fourier transform infrared (FTIR), and anthelmintic activity of methanolic and aqueous extract MCS formulation against earthworm Pheretima posthuma was evaluated. Result: As a result of FTIR analysis, MCS formulation showed the presence of coumarin, flavonoids, tannin, phenolic compound, saponin, quinone, and alkaloids. In investigating the anthelmintic action of formulation against adult Indian earthworms, the values of paralytic time and death time of formulation were less when compared to the positive control albendazole. Conclusion: The present work concludes that the MCS formulation acts as a more suitable herbal treatment against helminths infection.